Is the Measure to Phase Out Crude Palm Oil in RED II discriminatory based on the World Trade Organization Law? - Laras Thyrza Amandari; Yetty Komalasari Dewi (Yuridika, 2022)
The European Union enacted the Renewable Energy Directive 2018/2001 (RED II) policy under the pursuit of environmental protection. The authors will analyze how RED II is discriminative toward Indonesian trade of CPO, primarily within the concept of indirect land use change (ILUC), which restricts trade toward crude palm oil (CPO) whereas other domestic like products are exempted from such reduction. After the promulgation of this policy, Indonesia requested WTO to examine whether RED II follows the international obligations set forward in WTO. The author will analyze non-discrimination under WTO Law, specifically based on the provisions of Article 2.1, 2.2, and 5.1 Technical Barriers to Trade (TBT) Agreement as well as Article III:4, XX(b), and XX(g) of General Agreement on Tariffs and Trade (GATT) 1994, alongside with relevant jurisprudence of WTO case laws. This research is conducted through juridical-normative method, which utilizes library materials and secondary data. The outcome of this study shows that RED II does violate obligations of non-discrimination based on GATT and TBT due to differential treatment of like products that inflicts less favorable treatment and unequal opportunities of competition for CPO.